2004
DOI: 10.1007/bf03018239
|View full text |Cite
|
Sign up to set email alerts
|

Le nerf radial doit être anesthésié avant le nerf cubital pendant un blocage du plexus brachial au travers du canal huméral

Abstract: P Pu ur rp po os se e: : The brachial plexus block through the humeral canal as described by Dupré is indicated in hand and forearm surgery. This block requires a multi-stimulation technique that emphasizes the necessity of a rigorous and safe technique. Nerve injury associated with regional anesthesia can entail significant morbidity for patients. Thus, we investigated the brachial block sequence in terms of unintended nerve stimulation as a surrogate of potential nerve injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…In a previous study, we suggested blocking the deepest nerves before the superficial ones in order to improve the safety of the technique. 10 Our results confirm the efficacy of this sequence for rather different reasons.…”
Section: Discussionsupporting
confidence: 72%
“…In a previous study, we suggested blocking the deepest nerves before the superficial ones in order to improve the safety of the technique. 10 Our results confirm the efficacy of this sequence for rather different reasons.…”
Section: Discussionsupporting
confidence: 72%
“…105 When using a 4-nerve-stimulation, midhumeral approach, blocking the radial nerve before the ulnar nerve improves subsequent nerve localization. 106 Third, the relationship of the musculocutaneous nerve to the brachial plexus deserves special consideration, because it courses away from the axillary artery early and resides within the body of the coracobrachialis muscle or the fascial layers between the coracobrachialis and the biceps muscles. Anesthesia of the musculocutaneous nerve is best ensured by a separate injection into the belly of the coracobrachialis muscle 99,107 or by using direct ultrasound guidance.…”
Section: Axillary Blockmentioning
confidence: 99%